Pengaruh Pelatihan dan Lingkungan Kerja Terhadap Produktivitas Kerja Karyawan PT. Shenglu Zanmei International - Muhamad Diva Daniswara S; Iswati Iswati; Anis Fitriyasari; Emilia Pranata (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to test or analyze the influence of work environment training on the work productivity employees at PT Shenglu Zanmei International. The population in this study were all 53 employees in the production department of PT Shenglu Zanmei International, Surabaya City. The sampling technique for this research used a purposive sampling technique, thus the respondents for this research were 53 respondents from all permanent employees at PT Shenglu Zanmei International. This research uses primary data obtained through questionnaires and simple linear regression analysis methods as data analysis techniques. The data was processed using the Statistical for Product and Service Solution (SPSS) program. The results of the study showed that the physical work environment had a positive and significant effect on the work productivity variables of production employees at PT Shenglu Zanmei International.